(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2019)
The teaching department of the Dr Lucio Molas Hospital detected in its work environment the existence of problems related to the apparent “lack of communication”. Based on this concern, a first meeting took place in 2016 between communicators (educators–learners) and health professionals who work in that establishment. This intervention was framed within the subject Institutional Communication Management Workshop that was held in the hospital spaces, which led to situated learning and accompanied by the teacher. This communication experience set out to approach the work from the research paradigm-participatory action that considers important the “systematic return” to the participants in relation to the advances in the knowledge of the situation in which the “research educators” are involved. The communication intervention allowed to strengthen the dialogues between Hospital and University, as well as laid the foundations for the presentation of new work proposals, from the University Extension, Research and academic training.